Is Excess Free Cash Flow Over-Invested? Evidence from Borsa İstanbul - AYBARS, ASLI (My University, 2017)
In a perfect capital market, investments should not be related to cash flows of the firm. Investmentsshould only be determined by the amount of renewal investments required and growth opportunitiesavailable to the firm. Contrarily, due to the conflicts of interest between the managers and theshareholders, the theory on agency costs and free cash flow hypothesis propose that managers areinclined to over-use free cash flow, which is in excess of value-adding investments. It is claimed thatfirms invest their extra free cash flow on projects with returns below cost of capital of the firm. Someprior studies made on the topic implied the validity of this hypothesis. In other words, firm’s resourcesmight be wasted by means of over-investing. This study, based on a panel data of 154 Borsa Istanbulfirms observed between 2005-2015, confirmed that firms over-invest when there is free cash flowavailable in excess of growth opportunities and dividends. Prior studies have used mostly regressionmodels or Tobin’s q to estimate investment prospects of the firm. However, this study adopted a directmethod to estimate investment opportunities available to the firm.

Etkin çalışan sermaye piyasalarında, şirketin yarattığı nakit ile yatırımları arasında ilişki olması beklenmez. Yatırım miktarı, ihtiyaç olan yenileme yatırımları ve şirketin önündeki yatırım fırsatları ile belirlenir. Ancak, vekiller ve hissedarlar arasındaki çekişmelerden dolayı, vekâlet teorisine göre vekiller şirketin içinde kalan kullanım fazlası nakdi, karlı olmayan projelere yatırarak ziyan etmeye meyil ederler. Şirketlerin ihtiyaç fazlası nakdi sermaye maliyetinin altında getiri sağlayan projelere yatırdıkları öne sürülmektedir. Literatürdeki bazı çalışmalar bu tezin doğruluğunu teyit etmiştir. Diğer bir deyişle, şirketler gereğinden fazla yatırım harcaması yaparak ihtiyaç fazlası nakdi ziyan edebilmektedirler. Bu çalışma, 154 Borsa Istanbul şirketinin 2005-2015 yılları arasındaki verilerini panel analizinde kullanarak, dağıtılan kar payı ve karlı yatırım fırsatlarının üzerinde yaratılan nakdin gereğinden fazla miktarda yatırım harcamasında kullanıldığını göstermiştir. Literatürdeki önceki çalışmalar şirketlerin yatırım fırsatlarını regresyon ve Tobin’s q oranını kullanarak hesaplamıştır. Bu çalışma farklı olarak karlı yatırım fırsatlarını direkt olarak tahmin etmeye çalışmıştır.
Şirketler İhtiyaç Fazlası Nakdi Karsız Yatırımlarda mı Kullanıyor? Borsa İstanbul Üzerine Bir Çalışma